Chapter Парадоксальность Кроткой - Vassena, Raffaella (Biblioteca di Studi Slavistici, 2023)
A Gentle Creature's Paradox. The aim of this article is to analyze a smile as a mimetic, nonverbal facial expression. Although a smile most often displays joy and pleasure, it sometimes expresses emotions such as sadness, cruelty, anger, etc. This analysis aims to focus on the paradoxical "mistrustful, silent, and evil smile" of A Gentle Creature. Her smile marks the beginning of her life with the Pawnbroker and it is her companion until the end of her life. The paradox of smile illuminates other paradoxes such as that of communication (verbal/nonverbal, communication/its negation), of death (suicide and the icon, destruction/resurrection, silence/birth of words), of the Pawnbroker's story (author-narrator, narrative/story, fantastic/realistic, contradictions in the story), and of the event (real event/event in the narrator's mind).